2023
DOI: 10.1002/jeq2.20437
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic modeling indicates rapid glyphosate dissipation and sorption‐driven persistence of its metabolite AMPA in soil

Abstract: Residual concentrations of glyphosate and its main transformation product aminomethylphosphonic acid (AMPA) are often observed in soils. The factors controlling their biodegradation are currently not well understood. We analyzed sorption‐limited biodegradation of glyphosate and AMPA in soil with a set of microcosm experiments. A mechanistic model that accounts for equilibrium and kinetic sorption facilitated interpretation of the experimental results. Both compounds showed a biphasic dissipation with an initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Site U6, Bogue Phalia and U10, Yazoo River are described to have an intense use of glyphosate in their catchments, 23 which may lead to the accumulation of the more persistent AMPA. 24 This argument is supported when looking at the broad and similar concentration maxima of dechlorometolachlor, which is also more persistent than its parent metolachlor (Table S1). 25 The logarithm of the AMPA to glyphosate concentration ratio, log(A:G), at the Sope Creek (Site U12) and at the South Fork Iowa River near New Providence (U7) fluctuate around zero (median = 0.3) with either AMPA or glyphosate dominating at a time as can be expected for a small catchment.…”
Section: Concentration Patterns In the Usamentioning
confidence: 79%
“…Site U6, Bogue Phalia and U10, Yazoo River are described to have an intense use of glyphosate in their catchments, 23 which may lead to the accumulation of the more persistent AMPA. 24 This argument is supported when looking at the broad and similar concentration maxima of dechlorometolachlor, which is also more persistent than its parent metolachlor (Table S1). 25 The logarithm of the AMPA to glyphosate concentration ratio, log(A:G), at the Sope Creek (Site U12) and at the South Fork Iowa River near New Providence (U7) fluctuate around zero (median = 0.3) with either AMPA or glyphosate dominating at a time as can be expected for a small catchment.…”
Section: Concentration Patterns In the Usamentioning
confidence: 79%
“…Maccario et al [23] also found that soil texture did not have an impact on AMPA content. This could be explained by the soil's higher affinity to AMPA compared to glyphosate [14,83].…”
Section: Impacts Of Soil Properties and Cropping Systems On Glyphosat...mentioning
confidence: 99%
“…Glyphosate half-life is reported to range between 1 and 197 days, while AMPA half-life is between 23 and 958 days in temperate agricultural soils [12]. Once in the soil, AMPA is more resistant to biodegradation and has a higher affinity to soil particles compared to glyphosate, which increases its half-life in the soil [13,14]. Nonetheless, both molecules have similar physico-chemical properties with high water solubility, low lipophilicity, and very low volatilization potential [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, pesticide residues, which include DPs and metabolites, can usually be found in environmental compartments (Le Coadou et al, 2017). Diverse studies have confirmed that many DPs of pesticides can be more persistent, toxic and/or mobile than their parent compounds (Rani et al, 2020;Wimmer et al, 2023). Transformation reactions often lead to smaller, more polar and thus less hydrophobic molecules, increasing their water solubility.…”
Section: Introductionmentioning
confidence: 99%